2013
DOI: 10.1159/000345360
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Poststroke Seizures on Neurological Deficits: Magnetic Resonance Diffusion-Weighted Imaging Study

Abstract: Background: The impact of poststroke seizures on the neurological deficits related to ischemic stroke is not well known. It has been reported that following poststroke epilepsy, transient or long-lasting worsening of the poststroke sequelae may develop, but the underlying mechanism of deficit worsening has not been systematically studied by magnetic resonance diffusion-weighted imaging (MRI-DWI). Methods: From 2008 to 2009, 1,010 ischemic stroke patients were admitted to our stroke unit at the Ege University H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…DWI changes may occur in various cortical and cerebellar locations helping in the identification of epileptic foci (for example, aphasic seizure seemed to be associated with temporoparietal DWI changes based on the results of two case reports). 65,72 Multiple DWI changes could be associated with longer and recurrent seizures in IS patients as reported by Kumral et al 71 24 Asymptomatic ICH, younger age, high NIHSS Not reported ES was independent predictor of worse outcome Alberti et al 25 Hemorrhagic transformation Not reported ES did not influence mortality/disability Khealani et al 26 Not reported Not reported Early sepsis is associated with seizure recurrence Cordonnier et al 27 Not reported Not reported Epileptic seizures were independent predictors of new-onset dementia Chen et al 28 Cortical involvement, ASPECTS score 33 PoSERS scale Not reported The PoSERS appears to be a valuable tool to predict the risk for PSE within the first few days after a stroke de Reuck et al 34 No independent predictors Not reported -Stefanodou et al 35 Moderate and severe disability Not reported -Cheung et al 36 Male gender, cortical location (anterior)…”
Section: Brain Imagingmentioning
confidence: 69%
See 2 more Smart Citations
“…DWI changes may occur in various cortical and cerebellar locations helping in the identification of epileptic foci (for example, aphasic seizure seemed to be associated with temporoparietal DWI changes based on the results of two case reports). 65,72 Multiple DWI changes could be associated with longer and recurrent seizures in IS patients as reported by Kumral et al 71 24 Asymptomatic ICH, younger age, high NIHSS Not reported ES was independent predictor of worse outcome Alberti et al 25 Hemorrhagic transformation Not reported ES did not influence mortality/disability Khealani et al 26 Not reported Not reported Early sepsis is associated with seizure recurrence Cordonnier et al 27 Not reported Not reported Epileptic seizures were independent predictors of new-onset dementia Chen et al 28 Cortical involvement, ASPECTS score 33 PoSERS scale Not reported The PoSERS appears to be a valuable tool to predict the risk for PSE within the first few days after a stroke de Reuck et al 34 No independent predictors Not reported -Stefanodou et al 35 Moderate and severe disability Not reported -Cheung et al 36 Male gender, cortical location (anterior)…”
Section: Brain Imagingmentioning
confidence: 69%
“…A recent meta-analysis (including 26 Not reported Not reported Not reported Not reported Not reported Phenytoin and valproic acid were most commonly prescribed AEDs followed by carbamazepine Cordonnier et al 27 3/9 5/9 Not reported 1/9 4/9 were treated (2 with carbamazepine, 2 with valproic acid) Conrad et al 30 9 52 Not reported Not reported 17/27 1/27 Not reported Leys et al 53 15 20 2/19 7/19 7/19 Not reported Wang et al 22 0/123 51/123 21/123 51/123 Khealani et al 26 14/89 38/89 23/89 14/89 Conrad et al 30 10/23 10/23 3/23 Beghi et al 50 0/34 22/34 12/34 Dhanuka et al 52 12 54 11/24 9/24 2/24 2/24 Gupta et al 55 2/20 6/20 10/20 2/20 Horner et al 56 4/17 0/17 9/17 4/17 De Reuck et al 57 13/59 17/59 17/59 12/59 Velioglu et al 58 0/180 47/180 133/180 PLED, periodic lateralized epileptiform discharge. Hufnagel et al 61 Single-center 9 ADC decreased in the epileptogenic zoneGeneralized ADC changes after generalized seizures Konermann et al 62 Single-center 12 ADC decreased in the hippocampus on the seizure-onset side and in the parahippocampal gyrus on both sides Senn et al 63 Case report 1 ADC was higher in the affected hemisphere than on the other side Szabo et al 64 Single-center 10 Regional hyperintensity on DWI, and a reduction of the ADC in the hippocampal formation, the pulvinar region, and cortical regions Hong et al 65 Case report 1 ADC showed an increased signal in the left temporoparietal area Parmar et al 66 Single-center 10 DWI showed increased hippocampal signal and a decreased ADC in the same region Miligan et al 67 Single-center 10 Increased signal on DWI in the hippocampus ipsilateral to the seizure focus Variably restricted diffusion in the splenium and in gyral distribution Toledo et al 68 Single-center 8 Cortical temporoparietal hyperintensity in DWI and ipsilateral pulvinar lesions Lee et al 69 Case report 1 Hyperintensity lesions on DWI in the splenium and in the right parietal lobe Di Bonaventura et al 70 Single-center 10 DWI images revealed significant signal alterations depending on the location of ictal activity Kumral et al 71 Single-center 76 Multiple DWI changes and recurrent and l...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies should aim to clarify the impact of AED treatment on vascular-risk profile and rehabilitation. Another question is whether poststroke seizures can cause brain damage and thereby deterioration in neurological function, as is suggested by diffusion weighted imaging changes described in PSE patients with long-lasting neurological deterioration after seizures [Kumral et al 2013]. The impact of repeat early seizures on epileptogenesis after stroke is also not clear.…”
Section: Future Directionsmentioning
confidence: 99%
“…Seizure types were classified into 4 categories: (1) simple partial, (2) complex partial, (3) with secondary generalization, and (4) generalized tonic-clonic. SE was defined as a continuous seizure that lasted longer than 5 min, or multiple consecutive seizures lasting for a duration longer than 5 min without the patient regaining consciousness in between seizures [6, 7]. …”
Section: Methodsmentioning
confidence: 99%